Detection of Anti-HBV antibodies in patients treated by a private laboratory in Parnaíba, Piauí (Research, Society and Development, 2021)
The aim of the study was to evaluate the prevalence of serological markers of hepatitis B virus (HBV) infection in patients seen in a private laboratory in the city of Parnaíba, Piauí, from January to December 2018. This is an epidemiological cross-sectional and retrospective study. A total of 214 adult patients were included. The presence of the HBsAg antigen was detected in four (1.9%) patients while the immunity marker anti-HBs was detected in 92 (43%) patients. The presence of anti-HBc IgG was detected in 13 (6.1%) cases. In six (2.8%) patients it was possible to detect the concomitant presence of anti-HBs and total anti-HBc. The age of included patients ranged from 2 to 86 years (Mean: 36.88 years; SD: ± 14.77 years). The presence of HBsAg and anti-HBc IgG, which are markers of HBV infection, was detected more frequently in patients aged 46 to 59 years. On the other hand, the absence of these markers was observed in younger patients. The present study demonstrated a low HBsAg and anti-HBc prevalence, suggesting that the population evaluated has a lower endemicity of HBV infection.